Diseño, ficción y cultura : reflexiones sobre el diseño ficción - Baroni, Marcelo Gustavo (2023)
This research deals with a Speculative Design's subfield called Design Fiction (Dunne and Raby, 2013), a practice that can create a coherent fictional universe where exists a designed prototype in order to create a discursive space (Lindley and Coulton, 2015). Also, this work intends to investigate the different aspects that distinguish Design Fiction as a result of the social recognition of the "culture of design" by a diverse group made up of designers and other cultural agents. Besides, the Design Fiction methods are compared with other perspectives that include First and Second Generation Design Methods, Design Thinking and Speculative Design. This theoretical framework is also complemented by other authors linked to film studies, including Pezzella (2005) his research on the image, the artificial and everyday life, and Monterde (2001) for his conception of the cinematographic, spectatorial device and his notion of diegesis to propose a critical analysis of the Design Fiction's "diegetic prototypes". Finally, the hypothesis that leads this work is that this discipline redefines the design methods, through disciplinary crossovers that allow it to combine notions from film studies thought narrative themes referring to techno-social conflict in the culture of design context.